Automação de sistema de distribuição de ração em aviários de produção de ovos para incubatório - Barriquello, Juliano (2019)
Currently, with increased of the food consumption of animal origin, the productive processes need application of technologies to increase production and income. Within these productive processes, the eggs production for hatching stands out, it includes the production destined to the reproduction of the birds of cut and eggs laying, where the feed is the main input in relation to productivity and income. So, in search of optimization and improvement off eggs production and since there some need improvements related with automation in this type of the production, this paper presents information about the poultry sector regarding the implementation of a weighing and feed distribution system in an egg production poultry. Based on this, a feed distribution system was automated and it was composed of a mechanical prototype controlled by a Programmable Logic Controller (PLC) together with Supervisory System and sensors. Finally, it can be concluded that in a real application the system has a positive functioning in issues of monitoring and distribution of the feed, facilitating the daily work in the poultry, reducing the damage to equipment, occurring a better feeding of birds in the aspects of food quantity and a major contribution to eggs production.